Interpersonal Communication Between Volunteers and Street Children in the Community Save Sidoarjo Street Children - Uhti Benazir; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2022)
Communities in Indonesia are created from various kinds according to the benefits and objectives of the community, one of which is a social community, for example, is assistance given to people who are less fortunate and in need of assistance. it can be interpreted that the quality of communication is integrated with the quality of the community. This study aims to determine the interpersonal communication between volunteers and street children in the Save Street Child community in Sidoarjo. The results of this study show that interpersonal communication between volunteers and street children is very effective with openness, empathy, support, a sense of positivity, and equality.